Konsentrasi Logam Berat Kadmium (CD) Pada Sedimen Di Daerah Sekitar Perairan Pelabuhan Kapal Barang Talumolo Kota Gorontalo - Sri Yuningsih Noor (Gorontalo Fisheries Journal, 2018)
The aim of this research was to determine the concentration cadmium (Cd) in the sediments in the area of Talumolo Cargo Ship Port, Gorontalo. The method used in this research was descriptive analysis as a mean of describing and explaining the result which has already been obtained then compare it with the quality standard set by The Department of Conservation and Natural Resources Melbourne (2004) and ant the quality standard set by Dutch Quality standars For Metals in Sedimen (IADC/CEDA, 1997). The results showed that the concentration cadmium (Cd) in the sediments in the area of Talumolo Cargo Ship Port, Gorontalo City, the highest was found at point 2 (the sediment in the harbor area) with the calculation reached 0.3229 ppm, and the second was found at the third point (sediment in the sea area) with 0.2225 ppm, while the lowest cadmium was in the first point (Bone estuary) with the number 0.2027 ppm. The concentrations of cadmium (Cd) in the sediments in the area of Talumolo Cargo Ship Port, Gorontalo still not reached the quality standard set by The Department of Conservation and Natural Resources Melbourne (2004) which was set as 1ppm, and the quality standar set up by the Dutch Quality Standars For Metals in Sediment, IADC/CEDA, (1997) which was 0.8 ppm.Â Keywords : Heavy metals, Cadmium, Sediment, Talumolo, Gorontalo